Lymph Node Metastases of Medullary Thyroid Cancer: Role of Calcitonin in the Washout Fluid of Fine-Needle Aspiration. (4th April 2020) - Marques, Bernardo; Cunha, Nuno; Martins, Raquel G.; Elvas, Ana Rita; Couto, Joana; Santos, Jacinta; Martins, Teresa; Moniz, Ana Paula; Ilhéu, Olga; Valido, Frederico; Rodrigues, Fernando
Abstract : Introduction . The diagnostic value of calcitonin (CT) measurement in fine-needle aspirate washout (FNA-CT) for medullary thyroid cancer (MTC) lymph node (LN) metastases remains to be determined. It may increase the diagnostic sensitivity, but data on this subject is sparse. Objective . Our study aimed to evaluate the utility of FNA-CT in the diagnosis of LN metastases of MTC. Methods . We retrospectively investigated, in our institutional database, 69 consecutive FNA LN cytology from 42 patients who underwent FNA cytology and CT measurement in needle washout for suspicious LN between 2012 and 2017. Results . From the total of 69 FNA, 30 (43.4%) were performed in patients with personal history of MTC. MTC was detected in 19 FNA cytology (27.5%), and CT was detectable in needle washout in 23 cases (median = 2014 pg/mL; interquartile range = 490–15111 pg/mL). Based on the combined results of FNA-CT and FNA cytology, LN surgical resection was performed in 33 cases (47.8%). Histology reported MTC LN metastases in 21 lesions (63.6%). Regarding the diagnosis of MTC LN metastases, FNA cytology showed sensitivity of 81.8% and specificity of 97.9%, and FNA-CT demonstrated sensitivity of 100% and specificity of 97.9%. We determined through ROC analysis an optimal FNA-CT cut-off value of 23 pg/mL for the diagnosis of LN metastases (sensitivity 100%; specificity 100%). Conclusions . FNA-CT may be a valuable diagnostic tool for detection of MTC LN metastases, along with FNA cytology, and it should be included in the clinical workup of neck adenopathies in patients with MTC or with thyroid nodules.